An Analysis on the Kind of Tasks Found in Modul Pembelajar SMP Terbuka Bahasa Inggris: Modul 1 Its English Time for 8th Grade - Fauzan, Akbar (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2023)
Tasks on language textbooks are essential for displaying materials, assisting students in using the language, and fostering critical and creative thinking. This study's objective is to examine the task in the English textbook, Modul Pembelajar SMP Terbuka Bahasa Inggris: Modul 1 Its English Time, as well as the various types of assignments it offers in the eighth grade List making (24%) ordering and sorting (24%) comparing (20%) problem solving (32%) and sharing personal experiences (0%) were the least common task types offered in Modul Pembelajar SMP Terbuka Bahasa Inggris: Modul 1 It's English Time for 8th Grade, according to Willis's (2000) task taxonomy. In this study, we employed a descriptive qualitative and content analytic design. The study is also quantitative in that we calculated and tabulated the frequency and percentage of each sort of activity. The findings of this study are expected to increase English teachers' awareness of various task kinds that are crucial to the learning process. For developers to improve and add more communicative challenges to the existing English Learning teaching resources.